Métodos de geoprocessamento na avaliação da susceptibilidade do cerrado ao fogo - Pereira Júnior, Alfredo da Costa (Universidade Federal de São Carlos, 2002)
At the present, the Cerrado (a type of the Brazilian savannas) is burned on about 20 to 30% of its area during the dry season mainly owing to anthropic causes. Three simultaneous factors are needed for the burnings to happen: favourable meteorological conditions; availability of vegetation fuel; existence of an ignition source. This work studied the susceptibility of the Cerrado vegetation to fire with respect to parameters linked to the three factors: rainfall, relative air humidity and air temperature with respect to the meteorological conditions; vegetation coverage classes with respect to the biomass fuel; proximity to the roads and fire spots from previous days with respect to the ignition source. Location data for the fire spots obtained from the AVHRR/NOAA-12 channel 3 (3,7 mm) images were used as field truth. The study period was between May and October 1998. The study area was divided into 50 km x 50 km cells. The meteorological conditions occurring in 95% of the cells presents fire spots were: rainfall lower than 2 mm; 5-day cumulative precipitation lower than 25 mm; relative air humidity lower than 60%; air temperature higher than 28oC; more than one rainless day before the burning. More than 80% of the Cerrado were susceptible to the fire occurrence, with both locations with and without fire spots presented the minimum meteorological conditions favourable to the vegetation burning described in the literature: rainfall lower than 5 mm; 5-day cumulative precipitation lower than 20 mm; relative air humidity lower than 60%; air temperature higher than 25oC; A method for classifying the Cerrado vegetation coverage to fire susceptibility was also developed. This method was based on 2-weekly mosaics of the AVHRR/NOAA-14 Normalized Difference Vegetation Index (NDVI) and of the channel 3 images. Seven classes of vegetation coverage were discriminated and associated to four degrees of susceptibility: very low, low, medium and high. It was verified that 72% of the burning occurred in the high and medium susceptibility classes, which indicated satisfactory results on the preliminary development of this method. Lastly, the distance between the fire spots and two indicators of anthropic activity was analysed. The indicators were: roads and fire spots previously occurred. About a quarter of the fire spots occurred at up to 10 km from the roads in a area of 582,000 km2 surrounding the roads, which is about 27% of the Cerrado´s total area. On the same way, a quarter of the spots occurred at up to 10 km from the fire spots of the previous day, in an average area of 33,000 km2 at the burning spots surroundings. This area is about 2% of the total area of the Cerrado. In conclusion, the indicators of anthropic activity analysed here area good tools for studying the vegetation susceptibility to fire.
Keywords: Cerrado; Queimada; Fogo; AVHRR/NOAA; Parâmetros meteorológicos; Malha viária; Cerrado; Savanna; Burning; Fire; AVHRR/NOAA; Meteorology parameters; Roads; CIENCIAS BIOLOGICAS